New norterpene cyclic peroxides and a new polyketide from the marine sponge Diacarnus megaspinorhabdosa. (22nd June 2021) - Tang, Wei-Zhuo; Lu, Jing-Rong; Wang, Guang-Fei; Wu, Xing-Yu; Zhang, Wei; Yang, Fan; Lin, Hou-Wen
Graphical abstract: Highlights: Three new compounds were isolated from marine sponge Diacarnus megaspinorhabdosa . Dicarperoxides M and N represent a typical norterpene cyclic peroxide skeleton. Diacarnustin C comprises an α, β -unsaturated ester unit linked to a furan ring. Diacarnustin C is likely to arise from the rearrangement of diacarperoxide B. Dicarperoxides M and N showed moderate cytotoxicity against THP-1 and u937 cells. Abstract: Two new norterpenes dicarperoxides M and N and one new polyketide diacarnustin C were isolated from the marine sponge Diacarnus megaspinorhabdosa . Detailed spectroscopic analysis guided the elucidation of their structure. Structurally, dicarperoxides M and N incorporate a typical norterpene cyclic peroxide core, while diacarnustin C is noteworthy in that it contains an α, β -unsaturated ester unit linked to a furan ring. Dicarperoxides M and N displayed moderate cytotoxicity against THP-1 (IC50 values of 15.3 and 20.6 μM, respectively) and u937 cells (IC50 values of 13.4 and 25.7 μM, respectively).